2013
DOI: 10.1016/j.athoracsur.2013.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Clinical Practice Guideline in Treatment of Chylothorax in the Postoperative Congenital Heart Patient

Abstract: Background Chylothorax following congenital heart surgery is a common complication with associated morbidities, but consensus treatment guidelines are lacking. Variability exists in the duration of medical treatment and timing for surgical intervention. Methods Following institution of a clinical practice guideline for management of post-operative chylothorax at a single center, pediatric cardiothoracic intensive care unit (ICU) in June 2010, we retrospectively analyzed two cohorts of patients: those with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 19 publications
4
70
1
Order By: Relevance
“…Protocol-based management has been proposed to improve the outcomes of chylothorax, and studies have shown that implementing such management strategies led to reductions in chest tube utilization time and improvements in clinical outcomes [12][13][14]. We developed a management protocol and implemented it in September 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Protocol-based management has been proposed to improve the outcomes of chylothorax, and studies have shown that implementing such management strategies led to reductions in chest tube utilization time and improvements in clinical outcomes [12][13][14]. We developed a management protocol and implemented it in September 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Since we knew that cavopulmonary anastomosis procedures have a higher risk for prolonged pleural drainage, a more aggressive therapy with early initiation might be indicated for these patients; [3] hence, the need for a standard treatment protocol for chylothorax is crucial. Yeh et al [11] formulated a chylothorax algorhythm treatment in 2013 that produced an early diagnosis which reduced the time in the hospital as well as the use of mechanical ventilation. Their patients were fed with medium chained fatty acids when the amount of drainage was <20 mL/kg/day, but the oral intake ceased when the amount of drainage was >20 mL/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…[10] The optimal management of chylothorax is unclear because no prospective studies exist to aide in the choice of therapy since different protocols and strategies are followed in each center. [11,12] The primary modes of treatment include pleural space evacuation, the use of MCT oil-based formulas, enteric rest, and parenteral alimentation, [12,13] and these have shown a success rate of 77% within a maximum of 45 days, with an average time of approximately 12 days. [14] Previous studies have suggested that persistent chylous output for more than three weeks and lesions associated with elevated systemic venous pressure were risk factors for the failure of conservative management options.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of pediatric patients respond to medical therapy, although octreotide therapy and TPN carry their own risks [1,13]. Recommendations vary regarding indications and timing for surgical management with thoracic duct ligation or pleurodesis, but cases are generally considered refractory when effusion persists for more than 2 weeks despite conservative management [14]. Overall, these surgical interventions have a high success rate, and the main risk factor for death or chylothorax recurrence after surgery is thrombosis of the upper body venous vessels [15], thus confirming the importance of relieving such an occlusion whenever possible.…”
Section: Discussionmentioning
confidence: 99%